Measurement Algorithm of Two-Dimensional Wind Vector using Ultrasonic Transducers - Ding Xi-bo; Liang Jia-yi; Liu Jian; Guo Chao; Wang Tong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Ultrasonic wind speed measurement technique obtains more and more extensive use in the field of Meteorology and Environmental Protection etc. When designing an ultrasound wind vector instrument, synthesizing wind vector information, containing wind velocity vector and wind angle, is of prime importance to accomplish accurate measurement. This paper presents synthesis algorithm of ultrasonic 2D (two-dimensional) wind vector based on phase difference wind detection method, establishes mathematical model of wind speed, ultrasonic speed and phase difference, focuses on the analysis of the quadrant critical problem in the process of synthesizing wind angle.  And the ultrasonic phase difference wind speed and detection method proposed in this paper overcomes most disadvantages, e.g. complex circuit, troublesome signal processing etc., which exist in traditional time difference ultrasonic wind detection method. Through software emulation, the mathematical model established in this paper could calculate wind speed and direction precisely, based on 2D wind speed component. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1341